Clinical and sexual risk correlates of Mycoplasma genitalium in urban pregnant and non-pregnant young women: cross-sectional outcomes using the baseline data from the Women's BioHealth Study. (29th March 2018) - Trent, Maria; Coleman, Jenell S; Hardick, Justin; Perin, Jamie; Tabacco, Lisa; Huettner, Steven; Ronda, Jocelyn; Felter-Wernsdorfer, Rebecca; Gaydos, Charlotte A
Abstract : Objective: Research exploring the clinical and sexual risk correlates is essential to define universal standards for screening and management for Mycoplasma genitalium (MG). The objective of this study is to determine the baseline prevalence of MG and associated clinical risks using cross-sectional data. Methods: Adolescent and young adult women 13–29 years were recruited during clinical visits during which biological specimens were collected for Neisseriagonorrhoeae (NG) and Chlamydia trachomatis (CT) testing to provide vaginal specimens for MG and Trichomonasvaginalis (TV) testing. Demographic, clinical and sexual risk data were collected after obtaining written consent. MG was tested using the Hologic Gen-Probe transcription-mediated amplification–MG analyte-specific reagent assay and TV by the Aptima TV assay. Bivariate analyses were used to evaluate differences in MG prevalence based on pregnancy status, demographic factors, clinical symptoms, concurrent STI and sexual risk behaviour quiz score (maximum score=10). Results: 483 patients with a mean age of 22.4 years (SD 3.6) were enrolled. Most participants were not pregnant (66%) and asymptomatic (59%). MG was the most common STI (MG 16%, TV 9%, CT 8%, NG 1%). Neither pregnancy nor symptoms were predictive of STI positivity. Thirty-five percent of non-pregnant and 45% of pregnant adolescents ≤19 years were positive for any STI. Participants with MG were 3.4 times more likely to be co-infected with other STIs compared with those with other STIs (OR 3.4, 95% CI 1.17 to 10.3, P=0.021). Mean risk quiz scores for STI positive women were six points higher than those who were STI negative (β=0.63, 95% CI 0.36 to 0.90, P<0.001). There were no differences in risk scores for MG-positive participants compared with other STI positivity. Conclusion: MG infection was common, associated with STI co-infection and often asymptomatic, and pregnancy status did not confer protection.